Analisis faktor-faktor yang mempengaruhi ekspor minyak nabati di Provinsi Jambi - puspitasari, normalita; Nurjanah, Rahma; Mustika, Candra (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
This study aims to determine the effect of export prices, exchange rates, and economic growth on vegetable oil exports in Jambi Province, where this research was conducted for 18 years, starting from the period 2000-2018. This study uses multiple linear regression analysis with the Ordinary Least Square (OLS) method. Partial testing using statistical t-test and testing using the F statistic test. In addition, the classical assumption test was also carried out where the test was carried out using the Eviews 8 software. The results obtained showed that export prices, exchange rates, and economic growth together had a significant effect on the export of vegetable oil in Jambi Province. Meanwhile, partially export prices and exchange rates have a positive and significant effect on exports of edible oils in Jambi Province. Meanwhile, economic growth has a positive and insignificant effect on the export of vegetable oil in Jambi Province. Keywords: Vegetable oil exports, The value of vegetable oil exports, Export prices, Exchange rates, Economic growth